Labour law and the person : an agenda for social justice / Lisa Rodgers. - Rodgers, Lisa, 1979- (Bristol studies in law and social justice., 2024)
This book introduces an innovative approach to social justice for labour law centred on the concept of 'relational autonomy and vulnerability'. Highlighting the need to balance individual needs with societal needs and government involvement, the book sets an inclusive labour law agenda that adapts flawlessly to the ever-evolving labour market.